Skin Microbiome and Treatment-Related Skin Toxicities in Patients With Cancer: A Mini-Review - Richardson, Brianna N.; Lin, Jolinta; Buchwald, Zachary S.; Bai, Jinbing (Frontiers in Oncology, 2022)
The human skin hosts millions of bacteria, fungi, archaea, and viruses. These skin microbes play a crucial role in human immunological and physiological functions, as well as the development of skin diseases, including cancer when the balance between skin commensals and pathogens is interrupted. Due to the linkages between inflammation processes and skin microbes, and viral links to skin cancer, new theories have supported the role a dysbiotic skin microbiome plays in the development of cancer and cancer treatment-related skin toxicities. This review focuses on the skin microbiome and its role in cancer treatment-related skin toxicities, particularly from chemotherapy, radiation therapy, and immunotherapy. The current literature found changes in the diversity and abundance of the skin microbiome during cancer treatments such as radiation therapy, including lower diversity of the skin microbiome, an increased Proteobacteria/Firmicutes ratio, and a higher abundance of pathogenic Staphylococcus aureus. These changes may be associated with the development and severity of treatment-related skin toxicities, such as acute radiation dermatitis, hand-foot syndrome in chemotherapy, and immunotherapy-induced rash. Several clinical guidelines have issued potential interventions (e.g., use of topical corticosteroids, phototherapy, and non-pharmaceutical skin care products) to prevent and treat skin toxicities. The effectiveness of these promising interventions in alleviating treatment-related skin toxicities should be further tested among cancer patients.